Optimizing growth and biomass production of non-Saccharomyces wine yeast starters by overcoming sucrose consumption deficiency - Torrellas, Max; Pietrafesa, Rocchina; Ferrer-Pinós, Aroa; Capece, Angela; Matallana, Emilia; Aranda, Agustín (Frontiers in Microbiology, 2023)
The use of non-Saccharomyces yeasts as starters in winemaking has increased exponentially in the last years. For instance, non-conventional yeasts have proven useful for the improvement of the organoleptic profile and biocontrol. Active dry yeast starter production has been optimized for Saccharomyces cerevisiae, which may entail problems for the propagation of non-Saccharomyces yeasts. This work shows that the poor growth of Hanseniaspora vineae and Metschnikowia pulcherrima in molasses is related to a deficient sucrose consumption, linked to their low invertase activity. In order to address this issue, simple modifications to the cultivation media based hydrolysis and the reduction of sucrose concentration were performed. We performed biomass propagation simulations at a bench-top and bioreactor scale. The results show that cultivation in a hexose-based media improved biomass production in both species, as it solves their low invertase activity. The reduction in sugar concentration promoted a metabolic shift to a respiratory metabolism, which allowed a higher biomass yield, but did not improve total biomass production, due to the lower sugar availability. To evaluate the technological performance of these adaptations, we performed mixed grape juice fermentations with biomass produced in such conditions of M. pulcherrima and S. cerevisiae. The analysis of wines produced revealed that the different treatments we have tested did not have any negative impact on wine quality, further proving their applicability at an industrial level for the improvement of biomass production.